PENGARUH MEDIA QUIZALIZE TERHADAP MOTIVASI BELAJAR BAHASA ARAB SISWA KELAS XI DI SMA MUHAMMADIYAH 2 SIDOARJO - Divine Julia; Khizanatul Hikmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of using Quizalize on the Arabic learning motivation of 11th grade student at SMA Muhammadiyah 2 Sidoarjo. The background of this study is based on the low motivation of students in Arabic learning, which is still dominated by lecture methods, even though the school has eduquate technological facilities. This study used a quantitave approach with a quasi-experimental method and a One group Pretest-Posttest Design. The research subjects were 32 students in class XI-4. The instrument used was a learning motivation questionnaire with 20 statements based on five indicators, namely interest, attention, need for success, perseverance, and satisfaction. The data were analyzed using descriptive and inferential statistics using the Paired Sample t-Test. The results showed that the average score of student learning motivation increased from 70.19 on the pretest to 81.34 on the posttest. The t-test results showed a significance value of 0.000 (< 0.05), indicating a significant difference between before and after the use of Quizalize media. Thus, it can be concluded that Quizalize media has a positive and significant effect on increasing students' motivation to learn Arabic. This media is suitable as an alternative interactive learning tool to create a more enjoyable and motivating learning atmosphere.